2011
DOI: 10.1093/humupd/dmr043
|View full text |Cite
|
Sign up to set email alerts
|

Human leucocyte antigen class Ib molecules in pregnancy success and early pregnancy loss

Abstract: BACKGROUND The human leucocyte antigen (HLA) class Ib molecules, HLA-E, -F and -G, are expressed at the materno-fetal interface. Because of the apparent immunoregulatory functions of these proteins, they may be involved in successful acceptance of the semi-allogenic fetus during pregnancy. METHODS The literature on polymorphisms of the three genes, expression patterns of the proteins, and interactions with immune cell receptors have been evaluated to elucidate whether HLA-E, -F and -G are involved in the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 155 publications
(161 reference statements)
0
55
0
7
Order By: Relevance
“…9). Interestingly, it has been found recently that reduced or aberrant HLA-G expression seemed to be associated with certain complications of pregnancy, including the risk of miscarriage or preeclampsia (53)(54)(55)(56)(57)(58)(59). However, when soluble HLA-G isoforms were analyzed late in pregnancy, a low level of sHLA-G5 seemed to be associated with uncomplicated pregnancy, whereas in preeclampsia, the levels of sHLA-G5 were higher (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…9). Interestingly, it has been found recently that reduced or aberrant HLA-G expression seemed to be associated with certain complications of pregnancy, including the risk of miscarriage or preeclampsia (53)(54)(55)(56)(57)(58)(59). However, when soluble HLA-G isoforms were analyzed late in pregnancy, a low level of sHLA-G5 seemed to be associated with uncomplicated pregnancy, whereas in preeclampsia, the levels of sHLA-G5 were higher (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore McCormick et al, (2009) reported that sHLA-G actually inhibit trophoblast invasion of the maternal deciduas [13]. Dahl and colleagues in 2014 also reported that HLA-G may inhibit trophoblast invasion in concentrationdependent manners [14]. It could be that sHLA-G may not play a role in implantation, but rather in the maintenance of maternal immune tolerance to fetal antigen after implantation, because plasma sHLA-G levels increased with increasing trimester in both women who had normal delivery and women undergoing spontaneous abortion in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This results in the translation of four so-called membrane-bound isoforms (full length HLA-G1, and HLA-G2, -G3, and -G4 smaller forms), as well as three soluble isoforms (HLA-G5, -G6, and -G7). [13][14][15][16] Due to a stop codon in intron 4, these latter forms have neither transmembrane nor cytoplasmic translated domains. As a result, these secreted isoforms exhibit a small tail corresponding to the translated part of intron 4.…”
Section: Hla-g Is Expressed By Fetal-derived Trophoblastmentioning
confidence: 99%
“…[3][4][5][6][7][8] The reader may also refer to previous excellent reviews on the subject. [9][10][11][12][13] …”
mentioning
confidence: 99%